0446 Trends and Patterns in Prescriptions of Hypnotics for The Treatment of Insomnia in Japan: Analysis of A Nationwide Japanese Claims Database. (25th May 2022) - Okuda, Shoki; Qureshi, Zaina; Yanagida, Yukiko; Ito, Chie; Honma, Yuji; Tokita, Shigeru
Abstract: Introduction: Optimal treatment of insomnia is uncommon, given the lack of awareness regarding insomnia management. While the treatment landscape for insomnia has evolved following the introduction of orexin receptor antagonists (ORA), few studies have examined prescribing patterns of hypnotics. We analyzed data from a claims database to examine real-world use of hypnotics in Japan. Methods: Patients (aged ≥20 to <75 years old) with insomnia diagnosis, prescribed ≥1 hypnotic and continuous enrollment for ≥12 months before the index date were extracted from the JMDC claims database between April 1st, 2009 and March 31st, 2020. Patients were classified as new users of hypnotics or long-term users (prescribed the same mechanism of action [MOA] for ≥180 days). Trends (2010–2019) and patterns (2018–2019) in hypnotics prescriptions were analyzed. Results: The analysis comprised of 130, 177 new users and 91, 215 long-term users (2010–2019). Nearly all new users (97.1%–97.9%) were prescribed a single MOA in each year. In 2010, almost all new users (94.0%) of hypnotics were prescribed GABAA-receptor agonists (benzodiazepines [BZD] or z-drugs). The proportions of patients prescribed BZD declined over time (from 54.8% in 2010 to 30.5% in 2019), whereas those prescribed z-drugs remained stable (~40%). The proportion of patients prescribed a melatonin receptor agonist increased slightly (3.2% to 6.3%), while those prescribed ORA increased substantially (0% to 20.2%). Among long-term users, the proportion of patients prescribed BZD steadily declined over time, but more than half were prescribed BZD. Unlike new users, a lower proportion of long-term users were prescribed ORA (0% in 2010, 4.3% in 2019). Analyses using 2018–2019 data showed that a combination of multiple (≥2) MOAs was prescribed to a higher proportion (18.2%) of long-term users than new users (2.8%). The prescription patterns of hypnotics were comparable among patients stratified by age, sex, medical specialty, and psychiatric comorbidities. Conclusion: The present study showed distinct characteristics in the patterns and trends of the prescriptions of hypnotics among new users and long-term users in Japan. The high proportion of long-term BZD users suggests the need for educating clinicians about the optimal care pathway for insomnia. Support (If Any): MSD K.K., Tokyo, Japan